2017
DOI: 10.3233/isu-160812
|View full text |Cite
|
Sign up to set email alerts
|

Sustaining the growth of library scholarly publishing in a New University Press

Abstract: Abstract. In 2012, the University of Huddersfield Press presented a paper at the 16th International Conference on Electronic Publishing on its new open access journals platform. At the time, the Press was one of the only New University Presses (NUP) in the UK and one of the first to publish open access journals, open access monographs and sound recordings. This article discusses a number of emerging business models for NUPs before developing Hahn's programme and publication level business plan, which is then r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Of course, this is essential for any university press, but where the institution is investing in the press, the imperative is even stronger in order to demonstrate value for money. Graham Stone of the University of Huddersfield Press, at a presentation at the ELPUB2016 conference (Stone, ), attempted to quantify reputational benefits of Huddersfield's publishing, and concluded that Press outputs were at least partly responsible for £82.5 K of the University's Music School's Quality Related funding in 1 year. If it could be successfully argued that such publications would not have happened without the involvement and collaboration of the institution's own university press then this is a tangible benefit.…”
Section: Institutional Benefits and Reachmentioning
confidence: 99%
“…Of course, this is essential for any university press, but where the institution is investing in the press, the imperative is even stronger in order to demonstrate value for money. Graham Stone of the University of Huddersfield Press, at a presentation at the ELPUB2016 conference (Stone, ), attempted to quantify reputational benefits of Huddersfield's publishing, and concluded that Press outputs were at least partly responsible for £82.5 K of the University's Music School's Quality Related funding in 1 year. If it could be successfully argued that such publications would not have happened without the involvement and collaboration of the institution's own university press then this is a tangible benefit.…”
Section: Institutional Benefits and Reachmentioning
confidence: 99%